PERTANGGUNG JAWABAN RISIKO KERJA PADA KARYAWAN PEMADAM KEBAKARAN DALAM PERSPEKTIFAKAD IJARAH ‘ALA AL-AMAL - Ida Friatna; Jalilah; Tajul Muna Raya Guna (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2023)
The profession of a firefighter carries very high safety risks. Legal review in firefighting work using the Ijārah 'Ala al-A'mal agreement. The problems studied in this research are to find out, first, how to minimize work risks among Banda Aceh City Fire Department employees, second, what is the level of awareness of Banda Aceh City Fire Department employees regarding work risks, third, what forms of party responsibility exist? Banda Aceh City firefighters in the perspective of the Ijārah 'Ala al-A'mal Agreement. The research method used in this research is descriptive qualitative, and data collection was carried out using field research and library research. The data collection techniques used were interviews, observation and documentation. The research results show that efforts are made to minimize work risks with available facilities and infrastructure. Awareness of work risks among fire department employees is still lacking. The form of responsibility of the Banda Aceh City fire brigade in the perspective of the Ijarah 'Ala Al-Amal agreement based on the regulations used in work risk responsibility is in accordance with the Ijarah 'Ala Al-Amal agreement, however it is very unfortunate that there are differences in the social security obtained, which employees Civil servants get BPJS employment while contract employees do not get BPJS guarantees and any benefits so officers cannot submit claims for work accident insurance because officers are not insured by the government.